Measuring territorial cohesion trends in Europe: A correlation with EU Cohesion Policy - Medeiros, E. (2023)
Territorial cohesion is a formal EU policy goal since 2010, when it was placed in the Lisbon Treaty, alongside the long-term EU goals of economic and social cohesion. Understandably, by itself, a policy goal is irrelevant if it cannot be assessed. In this light, this article discusses potential methodological approaches to measure territorial cohesion trends in a given territory, their advantages and limitations, based on existing literature. It uses European NUTS 2 and the Portuguese and Polish NUTS 3 as concrete case studies to assess territorial cohesion trends from 2005 to 2020 via a Territorial Cohesion Index. As such, it presents an updated and unique picture on the territorial cohesion trends in Europe and in two specific EU member states, based on available data. It concludes that measuring territorial cohesion trends is challenging mainly due to lack of available data in certain key dimensions of territorial cohesion, but it is possible and needed.